DEVELOPING GOALKEEPERS’ REFLEX AND COORDINATION SKILLS THROUGH AUGMENTED REALITY (AR) - Bobomuradov Sobitjon Erkinovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the application of Augmented Reality (AR) technologies to enhance football goalkeepers’ reflexes and coordination skills. The study examines how AR can create interactive training scenarios, simulate real-game situations, and provide real-time feedback to optimize technical and cognitiveperformance. Additionally, the article discusses the benefits of integrating AR into goalkeeper training programs to improve reaction time, spatial awareness, and overall athletic efficiency.